Body size-dependent toxicokinetics and toxicodynamics could explain intra- and interspecies variability in sensitivity. (November 2015) - Gergs, André; Kulkarni, Devdutt; Preuss, Thomas G.
Abstract: Ecological risk assessment of chemicals aims at quantifying the likelihood of adverse effects posed to non-target populations and the communities they constitute, often based on lethal concentration estimates for standard test species. There may, however, be intra- and interspecific differences in responses to chemical exposure. Here with the help of a toxicokinetic-toxicodynamic model, we explored whether differential body sizes might explain the observed variability in sensitivity between species and between life-stages of each individual species, for three model organisms, Daphnia magna, Chaoborus crystallinus and Mesocyclops leuckarti . While body size-dependent toxicokinetics could be used to predict intraspecies variation in sensitivity, our results also suggest that changes in both toxicokinetic and toxicodynamic parameters might be needed to describe differential species sensitivity. Accounting for biological traits, like body size, in mechanistic effect models will allow more accurate predictions of chemical effects in size structured populations, ultimately providing mechanistic explanations for species sensitivity distributions. Graphical abstract: Highlights: Body size-dependent intra- and interspecific responses to chemicals were explored. Body size-dependent toxicokinetics can predict intraspecies variation in sensitivity. Toxicokinetic-toxicodynamic parameters together might predict interspecies variation. Using biological traits in effect models allows better prediction of chemical effects. Abstract : We provide a first proof of concept for a predictive toxicokinetic-toxicodynamic modelling approach to extrapolate lethal effects across life-stages and species.